Sound System Culture and Local Creative Economy: An Ethnographic Study of Rural Communities in Sukorambi, Jember - Anik Fitri Wismawati; Putri Amalia Febrianti; Riska Fitriyah (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2023)
This study explores how participatory spaces are formed within the sound system communitythrough the Sound Miniature Contest in Sukorambi Village, Jember, Indonesia. Emerging fromshared interests and collective enthusiasm for sound technology, this community has evolvedinto a distinctive cultural movement that integrates leisure, creativity, and localentrepreneurship. Using a qualitative ethnographic approach, data were collected throughparticipant observation, in-depth interviews, and documentation. The analysis employs apostmodern theoretical framework to interpret how sound system enthusiasts construct newforms of social interaction, identity expression, and symbolic capital. The findings reveal thatthissubcultural practice not only redefinesrural youth engagement and social cohesion but alsocontributes to the dynamics of the local creative economy. Ultimately, the study demonstratesthat the sound system culture in Sukorambi functions as a hybrid arena where culturalexpression, technology, and economic participation converge, thereby stimulatingcommunity-based economic growth.